Determinants of quality of life in primary family caregivers of patients with advanced cancer: a comparative study in southern China - Lin, Jiaqi; He, Zhuoxin; Fan, Guanhua (Frontiers in Public Health, 2023)
Objective To examine and compare the quality of life (QoL) of the primary family caregivers (PFCs) of inpatients with advanced cancer and the PFCs of home hospice patients with advanced cancer and to analyze the determinants of QoL. Methods Four hospices and three comprehensive or tumor hospitals in Guangdong Province, China were research sites. QoL was measured using paper-based and online questionnaires. Multiple stepwise linear regression was used to analyze the determinants of QoL of PFCs. Results The PFCs of inpatients had significantly better QoL than did the PFCs of home hospice patients (p < 0.01). One-way ANOVA results indicated the following: for the PFCs of inpatients, PFC age (t = 2.411, p < 0.05), type of relationship with patient (F = 2.985, p < 0.05), and family economic situation (F = 3.423, p < 0.05) significantly affected PFCs’ QoL; for the PFCs of home hospice patients, family economic situation (F = 3.757, p < 0.05) and care experience (t = 2.021, p < 0.05) significantly affected PFCs’ QoL. A multiple stepwise linear regression was conducted: for the PFCs of inpatients, family economic situation and whether the PFC was the patient’s immediate family member were included as predictors of QoL; for the PFCs of home hospice patients, family economic situation and care experience were included as predictors of QoL. Conclusion Our findings can help improve the home hospice care service model in mainland China. In particular, the QoL of the PFCs of home hospice patients requires urgent attention. The PFCs of home hospice patients requires more nursing guidance and interactions with community.